Recognition and the Fleeting Glimpse of Intimacy: Tracing the Chaplain’s Response to Ungrieved Death - Coble, Richard (Journal of pastoral care & counseling, 2015)
The article traces the response of the hospital chaplain witnessing ungrieved death. Linking grief with cultural recognition, the article analyzes the absence of grief on the occasion of death within outcast social spheres. It then outlines the ways chaplains both participate in the cultural norms that render lives ungrievable and, conversely, in the solidarity of God, who cares for every life and death. The article closes by situating the chaplain as a liminal figure and proposing liminality itself as an opportunity for solidarity.